2019
DOI: 10.1111/tpj.14593
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ubiquitylomics approach for characterizing the dynamic change and extensive modulation of ubiquitylation in rice seed germination

Abstract: Summary During seed germination, cells embark on extensive post‐transcriptional and post‐translational modifications (PTM), providing a perfect platform to study these events in embryo rebooting from relative quiescenct to highly active state. PR‐619, a deubiquitylase inhibitor, delayed the rice seed germination and resulted in the accumulation of ubiquitylated proteins, which indicated the protein ubiquitylation is involved in this process. Using the K‐Ɛ‐GG antibody enrichment method integrated with high‐reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 88 publications
3
20
0
1
Order By: Relevance
“…Protein ubiquitination is another important protein modification known to negatively affect the stability of proteins with a crucial role in germination, such as DELLAs [14,229], ABI3 [230] and ABI5 [231,232]. Changes in ubiquitination were detected in more than 1000 proteins during rice seed germination and most changes occurred at 12 hai, as observed previously for phosphorylation [233]. Sumoylation has also been demonstrated to play a role in this process by providing stability to ABI5 and MYB30 TFs.…”
Section: Germination Control By the Epigenomesupporting
confidence: 58%
“…Protein ubiquitination is another important protein modification known to negatively affect the stability of proteins with a crucial role in germination, such as DELLAs [14,229], ABI3 [230] and ABI5 [231,232]. Changes in ubiquitination were detected in more than 1000 proteins during rice seed germination and most changes occurred at 12 hai, as observed previously for phosphorylation [233]. Sumoylation has also been demonstrated to play a role in this process by providing stability to ABI5 and MYB30 TFs.…”
Section: Germination Control By the Epigenomesupporting
confidence: 58%
“…At the protein level, only four proteins overlapped between DFASPs and DAPs, which belonged to different metabolic processes (Supplementary Table 9). A quantitative ubiquitylomics analysis of rice seed germination revealed that protein abundance in the ubiquitylome is not correlated with that in the proteome (He et al, 2020). Consistent with this phenomenon, we did not find a significant correlation between the overlapping succinylations and proteins (Supplementary Figure 5).…”
Section: Pathway and Protein-level Convergence Of Succinylation And Asupporting
confidence: 77%
“…The protein kinases [38,39], protein phosphatases, and transcription factor [40,41] classes of protein serve to regulate many physiological processes [42]. Seed germination marks the starting point of plant growth and development, which is regulated by some proteins [43]. These proteins regulate catabolism [44], energy metabolism [45], anabolism, and defense reactions [46].…”
Section: Discussionmentioning
confidence: 99%